Experimental food science - Penfield, Marjorie Porter (Food science and technology (Academic Press), 1990)
This textbook presents the scientific basis for understanding the nature of food and the principles of experimental methodology as applied to food. It reviews recent research findings and specific technological advances related to food. Taking an experimental approach, exercises are included at the end of each chapter to provide the needed experience in planning experiments. Emphasizing the relationships between chemical and physical properties, basic formulas and procedures are included in the appendix. Key Features: Demonstrates the relationships among composition, structure, physical properties, and functional performance in foods. Suggested exercises at the end of each chapter provide students with needed experience in designing experiments. Extensive bibliographies of food science literature. Appendix of basic formulas and procedures.